Terjemahan Beranotasi Buku Tokoh Tionghoa dan Identitas Indonesia: Dari Tjoe Bou San Sampai Yap Thiam Hien (2010) Karya Leo Suryadinata dari Bahasa Indonesia ke dalam Bahasa Tionghoa - Xuanyi, Lu (Paradigma: Jurnal Kajian Budaya, 2019)
This research is an annotated translation study. The author conducted an Indonesian- Chinese translation of two chapters of the biography named Tokoh Tionghoa & Identitas Indonesia: dari Tjoe Bou San sampai Yap Thiam Hien and gave annotations to important and necessary parts. The specific purposes of this research can be described as follows: (1) find the appropriate method to translate this source text; (2) find out proper translation techniques and provide reasons for choosing equivalence. In translating this biography, the author uses communicative translation (Newmark, 1988) and considers the dynamic equivalence theory of Nida and Taber (1982) as the main principle. Annotations are divided into six groups, namely: culturally charged words, phrases that are translated into Chinese idioms, proper nouns, metaphors, footnote, and sentences. To translate a text successfully, translators need not only a good mastery of languages but also broad knowledge.